Examining the Phenomenon of Bullying among Students in the English Education Environment - Siti Nur'aini, Intan; Hana Fitriana Khoerunnisa; Alfaira Nazwa; Eka Nurhidayat (Papanda Publisher, 2024)
This research aims to examine the phenomenon of bullying among students in the English Education Study Program. The research focuses on identifying the factors causing bullying and the impacts of bullying on students. To achieve these objectives, the researcher employs a qualitative approach, allowing an in-depth exploration of students' experiences and perspectives regarding campus environments and the bullying phenomenon. The researcher used surveys distributed to English Education students through Google Forms for data collection. The respondents of the survey were students from the English Education Program themselves. The survey was designed to gather detailed qualitative data about students' experiences, social conditions in the classroom, and their views on bullying. Therefore, this research is expected to contribute to the development of policies and strategies for creating a more inclusive and safe learning environment for all students.